Ammonium Iodide-Mediated Sulfenylation of 4-Hydroxycoumarins or 4-Hydroxyquinolinones with a Sulfonyl Chloride as a Sulfur Source - Guo, Tao; Wei, Xu-Ning (Synlett, 2017)
A novel ammonium iodide-induced sulfenylation of 4-hydroxycoumarins or 4-hydroxyquinolinones by using an aryl- or alkylsulfonyl chloride as the sulfur source gave a wide range of 3-sulfanyl-4-hydroxycoumarins or 3-sulfanyl-4-hydroxyquinolinones, respectively, in moderate to good yields. This method provides as a simple approach to the direct formation of C–S bonds, which is of high value and utility in the pharmaceutical industry.
Keywords: sulfanylhydroxycoumarins; sulfanylhydroxyquinolinones; C–S bond formation; sulfenylation; sulfonyl chlorides; ammonium iodide